Risk of Postpartum Hemorrhage in Hypertensive Disorders of Pregnancy: Stratified by Severity - Cagino, Kristen A.; Wiley, Rachel L.; Ghose, Ipsita; Ciomperlik, Hailie N.; Sibai, Baha M.; Mendez-Figueroa, Hector; Chauhan, Suneet P. (American Journal of Perinatology, 2024)
Objective We aimed to determine the composite maternal hemorrhagic outcome (CMHO) among individuals with and without hypertensive disorders of pregnancy (HDP), stratified by disease severity. Additionally, we investigated the composite neonatal adverse outcome (CNAO) among individuals with HDP who had postpartum hemorrhage (PPH) versus did not have PPH.Study Design Our retrospective cohort study included all singletons who delivered at a Level IV center over two consecutive years. The primary outcome was the rate of CMHO, defined as blood loss ≥1,000 mL, use of uterotonics, mechanical tamponade, surgical techniques for atony, transfusion, venous thromboembolism, intensive care unit admission, hysterectomy, or maternal death. A subgroup analysis was performed to investigate the primary outcome stratified by (1) chronic hypertension, (2) gestational hypertension and preeclampsia without severe features, and (3) preeclampsia with severe features. A multivariable regression analysis was performed to investigate the association of HDP with and without PPH on a CNAO which included APGAR <7 at 5 minutes, bronchopulmonary dysplasia, intraventricular hemorrhage, necrotizing enterocolitis, seizures, neonatal sepsis, meconium aspiration syndrome, ventilation >6 hours, hypoxic–ischemic encephalopathy, or neonatal death.Results Of 8,357 singletons, 2,827 (34%) had HDP. Preterm delivery <37 weeks, induction of labor, prolonged oxytocin use, and magnesium sulfate usage were more common in those with versus without HDP (p < 0.001). CMHO was higher among individuals with HDP than those without HDP (26 vs. 19%; adjusted relative risk [aRR] = 1.11, 95% CI: 1.01–1.22). In the subgroup analysis, only individuals with preeclampsia with severe features were associated with higher CMHO (n = 802; aRR = 1.52, 95% CI: 1.32–1.75). There was a higher likelihood of CNAO in individuals with both HDP and PPH compared to those with HDP without PPH (aRR = 1.49, 95% CI: 1.06–2.09).Conclusion CMHO was higher among those with HDP. After stratification, only those with preeclampsia with severe features had an increased risk of CMHO. Among individuals with HDP, those who also had a PPH had worse neonatal outcomes than those without hemorrhage.Key Points
Keywords: blood loss; coagulopathy; hysterectomy; maternal morbidity; preeclampsia